2018
DOI: 10.7150/jca.25883
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of frozen section analysis of borderline ovarian tumors: a meta-analysis with emphasis on misdiagnosis factors

Abstract: Objective: First, to evaluate the sensitivity and positive predictive value (PPV) of intra-operative frozen section (FS) diagnosis in borderline ovarian tumors (BOTs), and to explore the factors affecting the diagnostic accuracy. Second, to assess the clinical outcomes of misdiagnosed BOT patients.Methods: We performed a retrospective study of all patients diagnosed as BOT through FS or paraffin section (PS) at Qilu Hospital between January 2005 and December 2015. Clinical and pathologic data were extracted. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
4
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 38 publications
4
23
4
3
Order By: Relevance
“…The sensitivity and PPV of FS analysis for BOT were 66.6% and 69.2%, respectively. These values are relatively lower than has been previously reported (sensitivity between 75 and 93% and PPV between 88 and 95%) (24,25). Underdiagnosis was identified in 30 patients (16.8%) in the present study, which was relatively higher than that reported in previous studies (24).…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…The sensitivity and PPV of FS analysis for BOT were 66.6% and 69.2%, respectively. These values are relatively lower than has been previously reported (sensitivity between 75 and 93% and PPV between 88 and 95%) (24,25). Underdiagnosis was identified in 30 patients (16.8%) in the present study, which was relatively higher than that reported in previous studies (24).…”
Section: Discussioncontrasting
confidence: 83%
“…These values are relatively lower than has been previously reported (sensitivity between 75 and 93% and PPV between 88 and 95%) (24,25). Underdiagnosis was identified in 30 patients (16.8%) in the present study, which was relatively higher than that reported in previous studies (24). Such discrepancies in misdiagnosis could be explained by the relatively large tumor size and the fact that the most common histological subtype of the tumor in the present study was a mucinous tumor, which often contains benign, borderline, and malignant components together (24,26,27).…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…3,4 Besides, frozen-section readings will never achieve 100% of accuracy; however, despite the possibility of underdiagnosis and overdiagnosis, they may provide guidance in most cases. 2,5,6 A careful inspection of the abdominal and pelvic cavities should be performed for adequate staging and complete removal of the disease. Surgical staging generally includes cytologic washings, resection of the tumor, infracolic omentectomy and peritoneal biopsies.…”
Section: Introductionmentioning
confidence: 99%